Air Gauge Characteristics Linearity Improvement - Cz. J. Jermak; M. Jakubowicz; J. Dereżyński; M. Rucki (Journal of Control Science and Engineering)
This paper discusses calibration uncertainty and linearity issues of the typical back-pressure air gauge. In this sort of air gauge, the correlation between the measured dimension (represented by the slot width) and the air pressure in the measuring chamber is used in a proportional range. However, when high linearity is required (e.g., nonlinearity less than 1%), the measuring range should be shortened. In the proposed method, based on knowledge of the static characteristics of air gauges, the measuring range is kept unchanged but the nonlinearity is decreased. The static characteristics may be separated into two sections, each of them approximated with a different linear function. As a result, the nonlinearity is reduced from 5% down to 1% and even below.